Village Financial Reporting and Local Government Performance: The Mediating Role of Institutional Isomorphism - Syachbrani, Warka; Idrus, Mukhammad; Yusuf, Yulia Yunita; Ahmad (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study investigates the factors influencing the preparation and utilization of village financial reports and their impact on local government performance, emphasizing the mediating role of institutional isomorphism. Using a mixed-method sequential explanatory design, data were collected from 100 villages in South Sulawesi, Indonesia. The quantitative phase involved surveys distributed to village heads, treasurers, and financial staff, followed by qualitative interviews to deepen the understanding of identified factors. Data were analyzed using regression and thematic analysis. Results reveal that technical capacity, regulatory compliance, and institutional pressures significantly affect the use of financial reports in decision-making. Coercive, mimetic, and normative isomorphism mechanisms mediate the relationship between financial reporting and performance. The findings contribute to developing an institutional-based performance measurement model for village governments. This study provides practical recommendations for enhancing accountability, transparency, and effectiveness in village financial management.